Learning theology through the church's worship : an introduction to Christian belief - Okholm, Dennis L. (Baker Academic; Grand Rapids., 2018)
"Introduces students to Christian theology with sustained attention to the relationship between the church's doctrine and its worship, both historically and in practice"--
Liturgical ophthalmology, or why Christian theology and ethics begin and end with worship -- What is Christian theology? -- What are the sources for and the results of doing theology? -- Who is God? The doctrine of the Trinity -- Who Is Jesus Christ? Christology -- How did the world come into existence and what keeps it going? Creation and providence -- What is a human being? Theological anthropology -- What did Christ do for humans? Soteriology -- Who is the Holy Spirit and what does the Holy Spirit do? Pneumatology and the doctrine of sanctification -- What is the Church? Ecclesiology -- The Sacraments -- What is the future of God, humans, and the world? Eschatology.
Includes bibliographical references and index.
Keywords: Theology, Doctrinal -- Popular works